2017
DOI: 10.1101/191478
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prasinovirus attack of Ostreococcus is furtive by day but savage by night

Abstract: 19Prasinoviruses are large DNA viruses that infect diverse genera of green microalgae 20 worldwide in aquatic ecosystems, but molecular knowledge of their life-cycles is lacking. 21Several complete genomes of both these viruses and their marine algal hosts are now 22 available and have been used to show the pervasive presence of these species in microbial 23 metagenomes. We have analysed the life-cycle of OtV5, a lytic virus, using RNA-Seq 24

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 94 publications
2
8
0
Order By: Relevance
“…One exception was Phaeocystis , with its aggregate gene expression peaking during daylight hours while both the giant Phaeocystis globosa virus and its virophage peaked synchronously at night. In addition, a virus infecting Ostreococcus Clade OII (OtV2) had clear night peaks in transcription, a phenomenon that has only ever been observed in the laboratory in experiments with the most distant of other Ostreococcus species, O. tauri , when infected by OtV5 [84]. Cyanophages also had peak expression at night, as previously observed [12].…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…One exception was Phaeocystis , with its aggregate gene expression peaking during daylight hours while both the giant Phaeocystis globosa virus and its virophage peaked synchronously at night. In addition, a virus infecting Ostreococcus Clade OII (OtV2) had clear night peaks in transcription, a phenomenon that has only ever been observed in the laboratory in experiments with the most distant of other Ostreococcus species, O. tauri , when infected by OtV5 [84]. Cyanophages also had peak expression at night, as previously observed [12].…”
Section: Resultssupporting
confidence: 58%
“…Most of the reference viruses that were used for gene mapping in our analyses have been well characterized. In laboratory experiments, it has been shown that their lytic cycles are 24–48 h in length even under various forms of nutrient limitation [82, 84, 8789]. Hence, the detection of daily, closely synchronized transcription over more than two day/night periods suggests that a subset of each population of the major microbial players in this system, whether photosynthetic or not, was infected and lysed multiple times during the time course.…”
Section: Resultsmentioning
confidence: 99%
“…In the broader evolution picture, phylogenetic analyses of numerous chlorovirus genes indicate that the viruses most closely related to the chloroviruses are members of the prasinoviruses (also in the family Phycodnaviridae). This genus includes viruses that infect the smallest eukaryotic cell Ostreococcus, and related species in the class Mamiellophyceae (e.g., Derelle et al [243]). However, it is interesting that the chloroviruses evolved mainly by gene duplications and losses of genes belonging to large paralogous families (including movements of diverse mobile genetic elements), whereas Micromonas and Ostreococcus phycodnaviruses derive most of their genetic novelties though HGTs [244,245].…”
Section: Evolutionary Historymentioning
confidence: 99%
“…Replicating during the day also gives viruses the opportunity to use the alga’s photosynthetic products as energy for replication and assembly [ 57 , 74 ]. Aligning with these predictions are the studies carried out by Thyrhaug et al [ 90 ] (described in Section 3.3.2 ); Jacquet et al [ 116 ], who proved that viruses of the algae Emiliana huxleyi are characterized by a diel pattern with more progeny being produced during dusk; or Derelle et al [ 117 ] who showed diurnal patterns of infection in prasinoviruses. Furthermore, a homolog of the denV gene has been found in chloroviruses.…”
Section: Virus Evolutionmentioning
confidence: 75%